2019
DOI: 10.6000/1927-520x.2019.08.03.2
|View full text |Cite
|
Sign up to set email alerts
|

Buffalo Milk Yield, Quality, and Marketing in Different Agro-Climatic Districts of Bangladesh

Abstract: The study was aimed at assessing the productive performance of dairy buffalo and milk marketing approaches in different agro-climatic districts of Bangladesh. Three (03) districts of Bangladesh viz. Bhola, Mymensingh, and Dinajpur were chosen from the coastal, river basin and semi-arid region, respectively. A triangulation method of survey was used to collect the data and the components of the triangle were buffalo farms, buffalo farmers and buffalo herdsmen. The investigation duration was twelve (12) months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
(13 reference statements)
2
12
0
Order By: Relevance
“…Results revealed that 11% of participants were involved in milk collection and selling, 39% were directly associated with product manufacturing, and 50% were involved in milk collection and processing. This finding is similar to Rahman et al (2019), who reported that most of the coastal buffalo farmers sold buffalo milk directly to sweetmeat makers or Ghosh (middleman). However, 83% of family's income is derived from milk trading and processing business, whereas only 6% of participants' income comes from agriculture sources (Table 1).…”
Section: Characteristics Of Milk Traders and Processorssupporting
confidence: 89%
See 1 more Smart Citation
“…Results revealed that 11% of participants were involved in milk collection and selling, 39% were directly associated with product manufacturing, and 50% were involved in milk collection and processing. This finding is similar to Rahman et al (2019), who reported that most of the coastal buffalo farmers sold buffalo milk directly to sweetmeat makers or Ghosh (middleman). However, 83% of family's income is derived from milk trading and processing business, whereas only 6% of participants' income comes from agriculture sources (Table 1).…”
Section: Characteristics Of Milk Traders and Processorssupporting
confidence: 89%
“…Farmers are obliged to sell their milk to the Ghosh (middleman and sweetmeat processor) and local goalas at minimum cost. Besides, farmers take a loan from goala and product manufacturers with a condition of selling milk to them that limits the efficient milk marketing system (Rahman et al, 2019). The consumption pattern of milk and dairy products influences the processors and manufacturers to develop a particular type of product in their business.…”
Section: Introductionmentioning
confidence: 99%
“…Buffalo can convert coarse feed to meat and milk that resist natural calamities and diseases (Canbolat, 2012). Economic profits from buffaloes depend on their lifetime performances, and these performances could not reach it's potential if there is shortage of good husbandry practices and lower amount of feeds (Rahman et al, 2019). The farmers frequently raise buffaloes in a free-grazing system with tree leaves and natural grasses, but stall feeding at coastal areas in Bangladesh is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Still, no systematic linkage exists in the Bhola district among the producers, traders, and processors in response to the fluctuations in meat demand. Several studies have been undertaken in the Bhola district of Bangladesh focusing on the productive and reproductive performances of buffalo, socio-economic status of buffalo keepers, management practices, milk production systems (Uddin et al, 2016;Rahman et al, 2019), buffalo diseases like prevalence of balantidiasis (Biswas et al, 2020) and subclinical mastitis (Aliul et al, 2020). Buffalo buying-selling is a common phenomenon in the Bhola district caused by the affluent buffalo population.…”
Section: Introductionmentioning
confidence: 99%
“…The buffalo (Bubalus bubalis, L.) is an important livestock species in the world. Buffalo farming is highly emphasized for household income from milk for farmers' livelihood in Bangladesh [1]. Buffaloes have low reproductive performances caused by silent estrus, seasonal anestrous, delayed puberty, late post-partum conception, and a long calving interval.…”
Section: Introductionmentioning
confidence: 99%